Pädagogik und Geschlechterverhältnisse in der Pandemie. Analyse und Kritik fragwürdiger Normalitäten
In der Corona-Pandemie werden viele Themen zum Gegenstand öffentlicher Debatten, welche die Erziehungswissenschaft im Allgemeinen und die erziehungswissenschaftliche Frauen- und Geschlechterforschung im Besonderen seit Langem beschäftigen: Reproduktion sozialer Ungleichheit in Bildungskontexten, ungleiche Verteilung privater Sorge-, Erziehungs- und Betreuungsarbeit, Marginalisierung nicht-heteronormativer Lebensformen u.v.m. Das Ringen um eine Rückkehr zur „Normalität“ ist allgegenwärtig. Der Band zeigt aus geschlechtertheoretischer und erziehungswissenschaftlicher Sicht, dass diese Normalität zu den Bedingungen der Krise selbst gehört und eine Rückkehr zu einer solchen Normalität bestehende Herrschaftsverhältnisse fortsetzt. Obwohl die Öffnungen und Schließungen von Schulen und Kindertagesstätten oder die Belastung von Müttern durch „Homeoffice“ und „Homeschooling“ prominente Themen der politischen Streitigkeiten um die Pandemiebekämpfung und ihre Folgen sind und große mediale Aufmerksamkeit bekommen, sind erziehungswissenschaftliche Perspektiven und insbesondere Positionen der erziehungswissenschaftlichen Frauen- und Geschlechterforschung im Diskurs wenig präsent. Dies möchten die Herausgebenden des Bandes ändern. Ausgehend von Schlagworten wie „Systemrelevanz“ oder „Normalität“ und der Frage nach Retraditionalisierung und Professionalisierung vergeschlechtlichter Bildungs- und Erziehungsarbeit in der Pandemie, werden die genannten Problemstellungen offengelegt und weiterführende Fragestellungen und Perspektiven entwickelt. Vor diesem Hintergrund werden wissenschaftliche und politische Konjunkturen kritisch untersucht und mögliche Gegenentwürfe ausgelotet.

Health relevance of lowering postprandial glycaemia in the paediatric population through diet’: results from a multistakeholder workshop - Vinoy, Sophie; Goletzke, Janina; Rakhshandehroo, Maryam; Schweitzer, Lisa; Flourakis, Matthieu; Körner, Antje; Alexy, Ute; van Schothorst, Evert M.; Ceriello, Antonio; Zakrzewski-Fruer, Julia K.; Buyken, Anette (European Journal of Nutrition)
Abstract To summarize current knowledge and gaps regarding the role of postprandial glycaemic response in the paediatric population, a workshop was organized in June 2021 by the European branch of the International Life Science Institute (ILSI). This virtual event comprised of talks given by experts followed by in-depth discussions in breakout sessions with workshop participants. The main pre-specified topics addressed by the workshop organizing committee to the invited speakers and the workshop participants were: (1) the role of glycaemic responses for paediatric health, based on mechanistic insights from animal and human data, and long-term evidence from observational and intervention studies in paediatric populations, and (2) changes in metabolism and changes in dietary needs from infancy to adolescence. Each talk as well as the discussions were summarised, including the main identified research gaps. The workshop led to the consensus on the crucial role on health of postprandial glycaemic response in paediatric population. However, a lack of scientific data has been identified regarding detailed glucose and insulin profiles in response to foods commonly consumed by paediatric populations, as well as a lack of long-term evidence including the need for suitable predictors during childhood and adolescence to anticipate health effects during adulthood.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The Effect of Regular Consumption of Reformulated Breads on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Schadow, Alena M.; Revheim, Ingrid; Spielau, Ulrike; Dierkes, Jutta; Schwingshackl, Lukas; Frank, Jan; Hodgson, Jonathan M.; Moreira-Rosário, André; Seal, Chris J.; Buyken, Anette; Rosendahl-Riise, Hanne (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

CausalQA: A Benchmark for Causal Question Answering - Bondarenko, Alexander; Wolska, Magdalena; Heindorf, Stefan; Blübaum, Lukas; Ngonga Ngomo, Axel-Cyrille; Stein, Benno; Braslavski, Pavel; Hagen, Matthias; Potthast, Martin (Proceedings of the 29th International Conference on Computational Linguistics)
At least 5% of questions submitted to search engines ask about cause-effect relationships in some way. To support the development of tailored approaches that can answer such questions, we construct Webis-CausalQA-22, a benchmark corpus of 1.1 million causal questions with answers. We distinguish different types of causal questions using a novel typology derived from a data-driven, manual analysis of questions from ten large question answering (QA) datasets. Using high-precision lexical rules, we extract causal questions of each type from these datasets to create our corpus. As an initial baseline, the state-of-the-art QA model UnifiedQA achieves a ROUGE-L F1 score of 0.48 on our new benchmark.

Binary Hermitian Lattices over Number Fields - Kirschmer, Markus; Nebe, Gabriele (Experimental Mathematics)
In a previous paper the authors developed an algorithm to classify certain quaternary quadratic lattices over totally real fields. The present article applies this algorithm to the classification of binary Hermitian lattices over totally imaginary fields. We use it in particular to classify the 48-dimensional extremal even unimodular lattices over the integers that admit a semilarge automorphism.
Keywords: General Mathematics

Domain-aware Text Professionalization using Sequence-to-Sequence Neural Networks - Palushi, Juela

Propaganda Technique Detection Using Connotation Frames - Budanurmath, Vinaykumar

Dealing With Pre-Processing And Feature Extraction Of Time-Series Data In Predictive Maintenance - Manjunatha, Suraj

Analysis of Time-Series Classification in Conditional Monitoring Systems - Kaur , Parvinder

Prescribed signal concentration on the boundary: eventual smoothness in a chemotaxis-Navier–Stokes system with logistic proliferation - Black, Tobias; Wu, Chunyan (Calculus of Variations and Partial Differential Equations)
Keywords: Applied Mathematics; Analysis

Rapid preparation of self-supported nickel–iron oxide as a high-performance glucose sensing platform - Ni, Ming; Tan, Minyuan; Pan, Ying; Zhu, Chuhong; Du, Haiwei (Journal of Materials Chemistry C)
Nickel–iron oxide electrocatalysts prepared via a rapid electrodeposition are promising candidates for non-enzymatic glucose sensors.
Keywords: Materials Chemistry; General Chemistry

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Anne-Christine Brehm, Netzwerk Gotik. Das Ulmer Münster im Zentrum von Architektur- und Bautechniktransfer - Harnack, Maria (Blätter für württembergische Kirchengeschichte)

Im-materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag

Motorische Kompetenzen im Kindesalter: Monitoring, Intervention und Zusammenhänge mit der Selbstwahrnehmung - Strotmeyer, Anne
Motorische Kompetenzen und die Selbstwahrnehmung dieser sind zentral hinsichtlich der Ausbildung eines gesundheitsförderlichen Lebensstils. Bewegungsmangel im Kindesalter und motorische Defizite unterstreichen die Relevanz von Untersuchungen in diesem Forschungsfeld. In diesem Kontext besteht Forschungsbedarf, welcher an der jungen Forschungslinie zu motorischen Basiskompetenzen ansetzt. Daher zielt die vorliegende Arbeit auf die Untersuchung motorischer Basiskompetenzen im Kontext des Monitorings, der Intervention sowie der Untersuchung von Zusammenhängen mit der Selbstwahrnehmung. Es wurden konfirmatorische Faktorenanalysen durchgeführt sowie eine kompetenzorientierte Intervention für das mittlere Kindesalter konzipiert und evaluiert. Zudem fanden Varianzanalysen mit Messwiederholung und manifeste Pfadmodelle Anwendung. Neben der Bestätigung der faktoriellen Struktur des Tests zur Erfassung motorischer Basiskompetenzen (MOBAK 3-4), wurden Zusammenhänge mit endogenen sowie exogenen Faktoren nachgewiesen. Es konnte gezeigt werden, dass mit Hilfe der relativ kurzen Intervention positive Effekte auf die motorischen Basiskompetenzen erzielt werden können. Zudem zeigten sich moderate Korrelationen zwischen motorischen Basiskompetenzen und der Selbstwahrnehmung. Auf Grundlage dieser Befunde sollten im Bereich der Objektkontrolle vor allem motorische Kompetenzen und im Bereich der Lokomotion insbesondere die Selbstwahrnehmung zur Steigerung des Kompetenzlevels gefördert werden.

Lernerkorpora als Ressource in der quantitativen DaF-Forschung - Weber, Tassja (Vermitteln – Verbinden – Verstehen)

Lattice QCD noise reduction for bosonic correlators through blocking - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, Hai-Tao (Physical Review D)

Wundersame Materie. Neomaterialistische Perspektiven auf Relationalität, Wirkmacht und Sprache - Kostan, Anastassija; Hoppe, Katharina (Die Kraft des Staunens: der neue Materialismus in der Gegenwartskunst)

Die Sprache der Materie: Feministische Neomaterialismen zwischen diskursiver Intelligibilität und posthumanistischer Performativität - Kostan, Anastassija (Sociality-Materiality-Practice. Sozialität-Materialität-Praxis)